Short Note: Neonatal Emergencies - Bazie, Elsharif Ahmed; Osman, Mona Isam El-Din (Short Note: Neonatal Emergencies, 2024)
Cyanosis refers to a blue tone visible in the skin and mucous membranes, caused by desaturated or abnormal hemoglobin. Jaundice in the first 24 hours of life of a term newborn is pathologic. Cardiac disease presenting in the neonatal period are often congenital but can be acquired. Age at presentation of CHD varies with the underlying lesion, its impact on cardiac performance, and its dependence upon the ductus arteriosus. Neonatal sepsis can be categorized into early onset (occurring in newborns who are less than 72 hours of life) or late onset (occurring between 3 and 7 days of life).